Athénaïs the life of Louis XIV's mistress, the real queen of France - Hilton, Lisa (Little, Brown, 2002)
As lovely and charming as she was shrewd and calculating, Athénaïs de Montespan became the most powerful noblewoman of her day by brilliantly manipulating her forbidden role as mistress of King Louis XIV. With a lively narrative style that reads like fiction, Lisa Hilton reveals the woman behind the most dazzling days of the Sun King's reign. As a lover, Athénaïs risked the disgrace of adultery to conduct an affair that scandalized Europe. As a patron, she supported the leaders of the cultural renaissance. As a mother, she was the ancestor of most of the royal houses of Europe. The greatest beauty of her day, she lived publicly and sensationally until bizarre accusations of witchcraft forced her from grace in the "Affair of the Poisons," a mystery that remains unsolved. Athénaïs is an informative look at a true age of extremes and a woman who achieved the heights of power at a time when it was denied to most of her sex.
Includes bibliographical references (p. [335]-341) and index
Keywords: Louis <XIV, King of France, 1638-1715>; Montespan, Françoise-Athénaïs de Rochechouart de Mortemart <marquise de, 1641-1707>; Montespan, Françoise-Athénaïs de Rochechouart de Mortemart de -- 1641-1707; Frankreich; France -- Court and courtiers -- Biography; France -- Kings and rulers -- Paramours -- Biography; Biografie